ANGIOFIBROMA IN A 50-YEAR-OLD PATIENT - Raza, Syed Shahmeer; Owais, Syed Muhammad; Zahid, Salman; Haq, Ihtisham Ul; Manan, Haris; Qasim, Syeda Fizza; Ullah, Farhan; Hijaz, Asfandiar Shahrukh; Khan, Osamah Riaz (Journal of Ayub Medical College Abbottabad, 2017)
Juvenile Angiofibroma (JNA) is a benign tumour that tends to bleed and occur in the nasopharynx with most cases occurring in pre-pubertal and adolescent males 10 to 20 years. We present the case of a 50-year-old male shopkeeper who consulted the ENT out patients’ department (OPD) of Khyber Teaching Hospital (KTH) with the chief complaint of right sided nasal obstruction for the last 2.5 months which was associated with two episodes of epistaxis and diplopia which started 2 months back. He complained of right sided frontal and periorbital pain for the last 15 days. Past medical and surgical history was insignificant. Computerized Tomography (CT) scan without contrast and magnetic resonance imaging (MRI) showed finding consistent with a pedunculated tumour like growth. After baseline investigations, surgery was done and a Wilson’s incision was given and the mass was excised and sent to the lab for histopathological report which showed angiofibroma. The age of the patient shows that this is a very rare case of angiofibroma. Dissection of such tumours is important as they have propensity to bleed. Excision along with biopsy is the method of choice. Proper surgical techniques and use of better medical technology are required to make and early diagnosis. Further studies/case reports around the world would assert our findings that a nasopharyngeal angiofibroma can also be found in middle aged men. Keywords: Nasopharyngeal Angiofibroma; Nasopharynx; Nasal obstruction; Wilson’s Incision